1994
DOI: 10.1152/jappl.1994.77.4.1750
|View full text |Cite
|
Sign up to set email alerts
|

Sodium transport and fluid balance in lungs from normal and dystrophic hamsters

Abstract: Gravimetric and sodium transport characteristics of lungs from BIO 14.6 (dystrophic) hamsters were compared with those of lungs from golden Syrian (normal) hamsters at 30 and 150 days of age. Isolated perfused lungs were used to determine lung permeability and fluid balance differences between normal and dystrophic animals at both ages. Apparent permeability-surface area products for air space-to-vascular space sodium, sucrose, and fluorescein isothiocyanate-labeled dextran fluxes were compared in the four gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In view of the potentially toxic effects of radioactive compounds ( 125 I or 131 I), as used in previous studies (27, 29), we opted to utilize FITC-BSA to quantify protein leak from the vasculature into the pulmonary interstitium and alveoli of newborn lambs to assess the presence and extent of edema in vagally denervated and shamoperated animals. Similar agents have previously been used to investigate the progression of pulmonary edema and alveolar flooding in the rat and transport from the alveolar space to the vascular space in isolated perfused hamster lungs (17,52). An appropriate dose of FITC-BSA and frequency range of fluorescence to investigate the alveolar-capillary leak were validated in our laboratory, as discussed in METHODS. Previous studies suggested that the decreased Crs and poor gas exchange observed in vagally denervated animals might result from the presence of alveolar plasma proteins secondary to the capillary-alveolar leak causing surfactant system dysfunction (3,31).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the potentially toxic effects of radioactive compounds ( 125 I or 131 I), as used in previous studies (27, 29), we opted to utilize FITC-BSA to quantify protein leak from the vasculature into the pulmonary interstitium and alveoli of newborn lambs to assess the presence and extent of edema in vagally denervated and shamoperated animals. Similar agents have previously been used to investigate the progression of pulmonary edema and alveolar flooding in the rat and transport from the alveolar space to the vascular space in isolated perfused hamster lungs (17,52). An appropriate dose of FITC-BSA and frequency range of fluorescence to investigate the alveolar-capillary leak were validated in our laboratory, as discussed in METHODS. Previous studies suggested that the decreased Crs and poor gas exchange observed in vagally denervated animals might result from the presence of alveolar plasma proteins secondary to the capillary-alveolar leak causing surfactant system dysfunction (3,31).…”
Section: Discussionmentioning
confidence: 99%
“…The basic approach was to instill fluid containing tracer molecules into the air space of a lung undergoing single pass perfusion with a colloid-free solution and to measure the concentration of these molecules in the effluent (Goodman et al 1989;Waltz et al 1994). Guinea pigs that were either 7 or 30 days postnatal age were anesthetized with phenobarbital (0.5-1.0 mg/100 g body weight) and tracheotomized.…”
Section: Na + Movementmentioning
confidence: 99%
“…Apparent PS products were determined as described by Goodman and colleagues (Goodman et al 1989;Waltz et al 1994), using an adaptation of Fick's first law of diffusion: PS = C V Q/C A , where C V is the concentration of the tracer molecules in the perfusate effluent (dpm or fluorescence⋅s -1 ⋅cm -3 ), C A is the concentration of the tracers in the alveolar space (dpm or fluorescence⋅s -1 ⋅cm -3 ), and Q is the flow rate (cm 3 ⋅s -1 ). C A was corrected throughout the experiment by assuming that the lung weight changes reflected alveolar volume changes and that the solute loss from the air space was reflected by its appearance in the perfusate.…”
Section: Na + Movementmentioning
confidence: 99%
See 1 more Smart Citation